Proton Magnetic Resonance Spectroscopy at 3.0T in Rabbit With VX2 Liver Cancer: Diagnostic Efficacy and Correlations With Tumor Size - Liao, Ruikun; Tang, Zhuoyue; Li, Xiaojiao; Lv, Liang; Yang, Chao; Xiong, Hua; Zhou, Bi; Yu, Jiayi; Zhang, Dan (Frontiers in Oncology, 2022)
Purposes: To explore the diagnostic performance of Cho peak area (Cho Are), Cho peak amplitude (Cho Amp) and the combined approach (Cho Are_Amp) in detecting rabbit VX2 liver cancer at early stage via Hydrogen-1 proton magnetic resonance spectroscopy (1H-MRS), as well as the correlations between Cho Are, Cho Amp and tumor parameters like diameter and volume. Methods: Conventional magnetic resonance imaging (MRI) and MRS were performed to scan the VX2 liver cancer in rabbit. The tumor diameter was measured on T2-weighted imaging (T2WI), and the tumor volume was accordingly calculated. Cho Are and Cho Amp were obtained from MRS. The diagnostic performance of Cho Are, Cho Amp and Cho Are_Amp were assessed by receiver operating characteristic (ROC) curve and area under ROC curve (AUC), whereas specificity and sensitivity were calculated by the maximum Youden’s index. Spearman’s correlation analysis was performed to evaluate the relevance between tumor parameters (diameter, volume) and radiological indexes (Cho Are, Cho Amp). Results: ROC curve analysis showed that Cho Amp, Cho Are and Cho Are_Amp were effective in diagnosing VX2 liver cancer. The AUC of Cho Amp was 0.883, and the specificity and sensitivity were 0.944 and 0.722, respectively (P＜0.001). The AUC of Cho Are was 0.807, and the specificity and sensitivity were 0.778 and 0.833, respectively (P＜0.05). The AUC of Cho Are_Amp was 0.892, and the specificity and sensitivity were 0.833 and 0.833, respectively (P＜0.001). Cho Are and Cho Amp exhibited high positive correlation with tumor diameter and tumor volume, among which Cho Amp demonstrated better correlations to tumor diameter and tumor volume (r=0.956 and 0.946) than that of Cho Are (r=0.787 and 0.794). A high positive correlation was detected between Cho Are and Cho Amp (r=0.787), as well as tumor diameter and tumor volume (r=0.965). Conclusion: Cho Are_Amp can be used as effective tool in diagnosing early stage VX2 liver cancer with satisfied diagnostic accuracy. Cho Are and Cho Amp were positively correlated with tumor volume and tumor diameter. The results of this study provide further evidence that Cho Amp and Cho Are_Amp of MRS could aid in early diagnosis of liver cancer.